2001
DOI: 10.1159/000051038
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Bone Marrow Cells Can Contribute to Neointimal Formation

Abstract: To examine the source of smooth muscle-like cells during vascular healing, C57BL/6 (Ly 5.2) female mice underwent whole body irradiation followed by transfusion with 106 nucleated bone marrow cells from congenic (Ly 5.1) male donors. Successful repopulation (88.4 ± 4.9%) by donor marrow was demonstrated in the female mice by flow cytometry with FITC-conjugated A20.1/Ly 5.1 monoclonal antibody after 4 weeks. The arteries of the female mice were then subjected to two types of insult: (1) The iliac art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
137
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(146 citation statements)
references
References 17 publications
(20 reference statements)
5
137
0
4
Order By: Relevance
“…Because a major part of neointimal SMCs can be derived from bone marrow cells, [11][12][13] and circulating SMC progenitors have been demonstrated in humans, 14 we investigated whether SDF-1␣ affects the percentage of peripheral blood Sca ϩ lin Ϫ progenitor cells after carotid injury. Arterial injury triggered the rapid expansion of PBPCs in the circulation after 1 day (Figure 5A), which was prevented by the administration of a blocking SDF-1␣ mAb (4.9Ϯ0.8% versus 1.7Ϯ0.3% of mononuclear cells, nϭ4, PϽ0.01; Figure 5A), with the percentage remaining at levels of uninjured mice (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because a major part of neointimal SMCs can be derived from bone marrow cells, [11][12][13] and circulating SMC progenitors have been demonstrated in humans, 14 we investigated whether SDF-1␣ affects the percentage of peripheral blood Sca ϩ lin Ϫ progenitor cells after carotid injury. Arterial injury triggered the rapid expansion of PBPCs in the circulation after 1 day (Figure 5A), which was prevented by the administration of a blocking SDF-1␣ mAb (4.9Ϯ0.8% versus 1.7Ϯ0.3% of mononuclear cells, nϭ4, PϽ0.01; Figure 5A), with the percentage remaining at levels of uninjured mice (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Application of a blocking SDF-1␣ mAb reduces neointimal area and neointimal SMC content, which indicates an important role during the progression of accelerated atherosclerosis. Because SDF-1␣ is important in the homeostasis of bone marrow homing and mobilization of progenitor cells, 7,19 and neointimal SMCs originate from a bone marrow source of progenitors, [13][14][15] we studied the effect of SDF-1␣ on progenitor cell mobilization and recruitment after carotid injury. We found that the expansion of PBPCs in the circulation and the accumulation of injected PBPCs in established neointimal lesions were mediated by SDF-1␣.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These messages govern the plaque formation that includes clonal accumulation of SMCs within the intima. 49 Recent evidence indicates that besides migration of the existing SMCs from the vessel's media to the intima, circulating bone marrow cells 50 and the vascular progenitor cells present in the adventitia of all arteries, are other sources of intimal SMCs. 51 In coronary arteries, SMCs form a fibrous cap that, if afflicted by MMPs and IFN-␥, may lead to the plaque rupture.…”
Section: Simionescu Endothelial Implications In Vascular Diseasementioning
confidence: 99%
“…Adventitial fibroblasts may also migrate to the intima, differentiate into myofibroblasts and contribute to neointima formation (27,28). Moreover, several groups have shown that bone marrow-derived vascular cells with some characteristics of VSMCs accumulate in the neointima of transplant vasculopathy and in a severe vascular injury animal model (29)(30)(31). Cell division involves two consecutive processes: interphase, ie, the time between two mitosis (M) periods, and the mitosis itself, ie, the process of cell division.…”
Section: Early Cell Cycle Progression (G0/g1/s Phase)mentioning
confidence: 99%